Archival Analysis of Corporate Social Responsibility Research: The Romanian Perspective - Camelia Iuliana Lungu; Chirata Caraiani; Cornelia Dascălu; Dan Turcu; Mihaela Turturea (Journal of Accounting and Management Information Systems (JAMIS), 2016)
Corporate Social Responsibility has emerged as one of the main topics of the current economic environment, hence the accounting literature. This paper establishes the characteristics of CSR research and the contribution of authors to the incremental knowledge within Romanian context. It is a retrospective review of mapping out the defining landscape of Romanian research focused on CSR as the most referred to sustainability issue. The paper employs the archival analysis and literature review methods in order to answer its purpose. This research adds to prior published literature reviews in accounting by focusing on the particular topic of CSR. A range of information collected from 186 papers with Romanian authors, published in 46 scientific journals is analyzed. Results reporting authors' affiliation, content, research methods, citations and references exhibit a tangible and continuous interest for the topic. The paper is expected to be of a particular interest to new researchers in sustainability accounting.
Keywords: M14; M40; Q56; 650; Corporate social responsibility; accounting; Romania; archival analysis; literature review; research methodologies.